2023
DOI: 10.1111/wvn.12629
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early palliative care on the quality of life in caregivers of cancer patients: A systematic review

Abstract: Background Maintaining caregivers' quality of life (QoL) is critical to sustaining the care needed for cancer patients. One of the interventions applied to cancer patients' caregivers is early palliative care (EPC). Aims This systematic review synthesized the implementation of EPC on the QoL of caregivers of cancer patients. Methods The search was undertaken using seven electronic databases: Medline, Embase, CINAHL, CENTRAL, Web of Science, Scopus, and ProQuest Dissertation & Theses (PQDT). The search strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…15,16 Ultimately, the QoL and well-being of these caregivers are impaired. 16,17 A previous study of informal caregivers of patients with cancer reported that the prevalence of anxiety symptoms among this population reached 38.1%, and that the prevalence of depression symptoms ranged from 20.0% to 82.2%. 18 Furthermore, a study that compared the psychological burden of patients with cancer and that of their primary caregivers demonstrated that caregivers experience a degree of pain comparable to that of patients with cancer and an even higher levels of mental stress.…”
Section: Introductionmentioning
confidence: 89%
“…15,16 Ultimately, the QoL and well-being of these caregivers are impaired. 16,17 A previous study of informal caregivers of patients with cancer reported that the prevalence of anxiety symptoms among this population reached 38.1%, and that the prevalence of depression symptoms ranged from 20.0% to 82.2%. 18 Furthermore, a study that compared the psychological burden of patients with cancer and that of their primary caregivers demonstrated that caregivers experience a degree of pain comparable to that of patients with cancer and an even higher levels of mental stress.…”
Section: Introductionmentioning
confidence: 89%
“…Globally, China has the highest number of new cancer cases and deaths, and the cancer burden is increasing 3. Palliative care is a philosophy of care aimed at enhancing the quality of life for patients with serious illnesses and their families 4 5. The 2017 National Comprehensive Cancer Network clinical practice guidelines on palliative care strongly emphasise the early integration of palliative care into overall oncology treatment 6.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Palliative care is a philosophy of care aimed at enhancing the quality of life for patients with serious illnesses and their families. 4 5 The 2017 National Comprehensive Cancer Network clinical practice guidelines on palliative care strongly emphasise the early integration of palliative care into overall oncology treatment. 6 Quality palliative care should encompass comprehensive support for patients and their families across physical, mental, spiritual and societal dimensions throughout the course of the illness.…”
Section: Introductionmentioning
confidence: 99%
“…EPC is the first model of care that has explicitly formalized the inclusion of the caregiver's QoL into the paradigm, as also recommended by WHO guidelines (26), since the time of the diagnosis and after the patient's death. As a consequence, the EPC, compared to the late PC, translates into a better output for the caregiver, as, has recently been demonstrated (for reviews, see 27,28). Notwithstanding, the construct of QoL from the caregiver's perspective has not been sufficiently investigated and there is paucity of validated measures in this area.…”
Section: Introductionmentioning
confidence: 99%